Proposta de modelo para diagnóstico de declínio organizacional baseados em fundamentos de excelência - Braga, Ana Carolina (2019)
This work aimed to develop a model for the diagnosis of Organizational Decline based on the foundations of Excellence. For this, a priori it was possible to build a theoretical model derived from variables of the Organizational Decline and Fundamentals of Excellence allowing the basis for the problem and proposing its measurement through two indicators: Organizational Satisfaction Indicator and Economic-Financial Indicator. After the construction of the theoretical model, it was necessary to apply the AHP method to allocate the influence factor weights in the application of two questionnaires to the managers of 15 companies belonging to a public transport network. Thus, after compiling the results, it was possible to verify in which phase of Organizational Health the companies were according to the model: Healthy Business Phase, Initial or susceptibility Business Phase, Business Preclinical Pathological Phase, Company Clinical Phase or Phase residual disability of the company. With the results of the x and y axes, it was found that the correlation level between the Organizational Satisfaction and Economic-financial variables has a strong correlation. Thus, it was observed that the study contributes both scientifically and empirically, because besides being considered original in view of the models already published, it had a diagnosis which is possible to perform an individual strategic analysis, as well as a comparative scenario between network companies. Thus, industries, interested companies and society can enjoy satisfactory results in the development of Quality Management improvement by Excellence, as it interferes with strategies to increase economic and financial factors and organizational satisfaction of the measured area.